The Influence of Transformational Leadershipof Principals and Teacher Achievement Motivation on Teacher Teaching Performance At SMA Dirgantara Center - Sabaruddin Chaniago; Widy Hastuty HS; Nirmalasari; Minasari Nasution (International Journal of Science, Technology & Management, 2020)
This research aims to findout the influence of transformational leadership and motivation to excel on teacher teaching performance at Dirgantara Senior High School Center. The population in the study was teachers at SMA Dirgantara Center which numbered 34 teachers, while the sample determination technique was. So the sample in this study was 34 people. This type of research is quantitative research. Quantitative research is a study that aims to find out the degree of relationship and pattern/form of influence between two or more variables, where by this research will be built a theory that serves to explain, predict and control a symptom. As for the data sources in this study from primary data and secondary data. Where is the primary data from observations, interviews and questionnaires? While secondary data can be from documented data. Test results (t) or partial tests show that transformational leadership has a positive and significant effect on teacher teaching performance as well as motivational variables that also have a positive and significant effect on teacher teaching performance. Simultaneously transformational leadership and motivation of achievement havea positive and significant impact on the teaching performance of teachers. The result of determination is obtained a correlation regression value of 0.770, meaning that together transformational leadership and motivation to excel against the teaching performance of teachers at SMA Dirgantara Center has contributed to a close and positive level. Then the determination coefficient (R2) is 0.566 (56.6%). So it can be said that 56.6% variation of bound variables i.e. transformational leadership and motivation to excel on the model has a contribution to teacher teaching performance at SMA Dirgantara Center while the remaining 43.4% is influenced by other variables outside the model.